Assessment of adoption gap of Potato production Technology of Potato growers and their adoption Level - R P Singh; D.P. Singh; Satya Prakash; J.k. Arya (Journal of Soil and Water Conservation, 2022)
The present study was carried out during the year 2004-05 in Muzaffarnagar district of Uttar Pradesh. To assess the adoption gap in Potato Production Technology and the adoption level of Potato growers. Study reveals that the highest adoption gaps were found in plant protection measures of all categories Potato growers i.e. 72.10, 66.45, 57.06 and 52.06 percent marginal, small, medium and large potato growers respectively. The Lowest adoption gaps were found in soil selection of all categories Potato growers i.e. 34.28, 27.83, 18.14 and 10.86 percent marginal, small, medium and large potato growers. The average adoption gaps of marginal Potato growers were found highest 47.08 percent and lowest 26.80 percent of large potato growers. The adoption gaps of small and medium potato growers were 37.47 and 33.80 percent respectively. The highest adoption Level was found in Soil Selection of Large Potato Growers 89.14 Percent and Lowest 65.32 percent of marginal Potato growers. The adoption level of small and medium Potato growers were 72.17 and 81.86 percent respectively. The average adoption level as large Potato growers were found highest 73.20 percent and lowest 52.92 percent of Marginal Potato growers the adoption level of small and medium Potato growers 62.43 and 66.20 percent respectively.